2013
DOI: 10.5194/acpd-13-12485-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating global emission inventories of biogenic bromocarbons

Abstract: Emissions of halogenated very short-lived substances (VSLS) are poorly constrained. However, their inclusion in global models is required to simulate a realistic inorganic bromine (Bry) loading in both the troposphere, where bromine chemistry perturbs global oxidizing capacity, and in the stratosphere, where it is a major sink for ozone (O3). We have performed simulations using a 3-D chemical transport model (CTM) including three top-down and a single bottom-up derive… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 57 publications
5
34
0
Order By: Relevance
“…A similar discrepancy exists between CAM‐chem‐SD CHBr 3 and measurements obtained during CAST (not shown), which sampled altitudes below 8 km in the TWP during winter 2014 (Andrews et al, ). Previous evaluations of the Ordóñez et al () climatology, used by CAM‐chem‐SD for emissions of VSLS, have identified the potential to overestimate the actual emissions of CHBr 3 based on a comparison of model output to ground‐based and Southeast Asian aircraft observations (Hossaini et al, , ). However, CAM‐chem‐SD shows very good agreement with ATTREX measurements of CHBr 3 sampled at higher altitudes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar discrepancy exists between CAM‐chem‐SD CHBr 3 and measurements obtained during CAST (not shown), which sampled altitudes below 8 km in the TWP during winter 2014 (Andrews et al, ). Previous evaluations of the Ordóñez et al () climatology, used by CAM‐chem‐SD for emissions of VSLS, have identified the potential to overestimate the actual emissions of CHBr 3 based on a comparison of model output to ground‐based and Southeast Asian aircraft observations (Hossaini et al, , ). However, CAM‐chem‐SD shows very good agreement with ATTREX measurements of CHBr 3 sampled at higher altitudes.…”
Section: Resultsmentioning
confidence: 99%
“…Eyring et al () recommended that CCMI models incorporate the WMO 2011 best estimate for Br y VSLS of 5 ppt (Montzka et al, ) in one of two manners: either by explicitly including CHBr 3 and CH 2 Br 2 (the two major VSLS) in the model or by increasing the surface mixing ratio of CH 3 Br (a traditional, non‐VSLS source of bromine) by 5 ppt relative to baseline, to act as a surrogate for the additional bromine from VSLS. Recent studies have evaluated different emission inventories for VSLS that utilize more detailed emission schemes than recommended for the first phase of CCMI (Hossaini et al, , ; Lennartz et al, ), but model output from these recent runs are not provided in the public CCMI archive and are representative only of present time conditions. Here our focus is on the analysis of archived CCMI model simulations over long historical (1960–2010) and forecast (1960–2100) time scales conducted to study the interaction between climate change and atmospheric chemistry (Morgenstern et al, ; Revell et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the recent work of Hossaini and co-workers, 173 the TOMCAT 3D CTM was combined with the existing ocean emission inventories (see also section 3.2.2) of CHBr 3 and CH 2 Br 2 239,243245 to evaluate their tropospheric distribution and resulting stratospheric bromine injection. They reported a range of bromine injection to the stratosphere of ∼4.0–8.0 pmol/mol depending on the emission inventory, and quantitatively evaluated the different emissions by comparing the model results with available ground-based and aircraft observations from recent field campaigns.…”
Section: Recent Advances In Tropospheric Halogen Chemistrymentioning
confidence: 99%
“…The chemistry scheme includes a detailed description of the O x , NO y , Cl y , Br y , and HO x families, as well as source gases. The model also includes the brominated VSLS CH 2 Br 2 and CHBr 3 , which yield an additional 6 pptv of stratospheric bromine [ Hossaini et al, ]. The model includes a treatment of heterogeneous reactions on sulfate aerosols and polar stratospheric clouds.…”
Section: Model Setupmentioning
confidence: 99%